2016
DOI: 10.19044/esj.2016.v12n16p313
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment Of The Use, Benefits And Challenges Of The ‘Cash–Lite’ Policy, For Construction Projects In Anambra State, Nigeria

Abstract: The introduction of the ‘Cash-Lite; a cashless policy, by the Central Bank of Nigeria in 2011 has changed the modus operandi of the construction industry. This is because the industry is one of the few industries that deal mostly with cash. Hence, this study is aimed at examining the development and implementation of the Nigerian ‘Cash-Lite’ policy, with a view to ascertain its effects on construction practice. The study examined 300 construction stakeholders using questionnaires. Data obtained from these sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Nigeria being a developing country is confronted with a lot of problems and her construction industry is still struggling with a lot of intrinsic challenges, ranging from inadequate technical and managerial know-how to insufficient financial, material and equipment capital base [6]. According to [1] [7] the peculiar problems common to construction industries in sub-Saharan Africa (SSA) countries, are project financing, dearth of technical expertise, corrupt government and poor implementation of policies and programmes; these are challenges mitigating the development and growth of the sector and hence the contribution to the sustainable development.…”
Section: Literature Review Factors Affecting Construction Practice In Nigeriamentioning
confidence: 99%
“…Nigeria being a developing country is confronted with a lot of problems and her construction industry is still struggling with a lot of intrinsic challenges, ranging from inadequate technical and managerial know-how to insufficient financial, material and equipment capital base [6]. According to [1] [7] the peculiar problems common to construction industries in sub-Saharan Africa (SSA) countries, are project financing, dearth of technical expertise, corrupt government and poor implementation of policies and programmes; these are challenges mitigating the development and growth of the sector and hence the contribution to the sustainable development.…”
Section: Literature Review Factors Affecting Construction Practice In Nigeriamentioning
confidence: 99%
“…Hence, technologies are changing businesses today and making clients/consumers to break the normal norms of any business and every business requires a digital orientation, meaning a digital focus in all business processes and functions [19,20]. However, [21][22][23][24] observed that the construction and real estate sector, for example, ranks lowest in terms of digital maturity (i.e. Industry lags behind other industries in using ICT).…”
Section: Literature Review 21 Digital Transformation In Constructionmentioning
confidence: 99%
“…Construction industry according to [26] may be viewed as that sector of the economy which, through planning, design, construction, maintenance and repair, and operation, transforms various resources into constructed facilities. It is a sector of the economy that transforms various resources into constructed physical economic and social infrastructure necessary for socio-economic development [27,28]. The industry contributes significantly to the Gross Domestic Product (GDP) of any nation.…”
Section: Construction Industry and Digital Transformationmentioning
confidence: 99%